2019
DOI: 10.3390/insects10060182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Host Plants Reared under Elevated CO2 Concentrations on the Foraging Behavior of Different Stages of Corn Leaf Aphids Rhopalosiphum maidis

Abstract: Climate change is a major environmental concern and is directly related to the increasing concentrations of greenhouse gases. The increase in concentrations of atmospheric carbon dioxide (CO2), not only affects plant growth and development, but also affects the emission of plant organic volatile compounds (VOCs). Changes in the plant odor profile may affect the plant-insect interactions, especially the behavior of herbivorous insects. In this study, we compared the foraging behavior of corn leaf aphid (Rhopalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…During the feeding experiment, we observed that most of the alate adults remained stationary in the transparent plastic box, rather than moving to the barley seedlings as quickly as the apterous phenotypes. As we know, walking is the main way of apterous aphids moving to nearby plants in the field (Nottingham et al ., 1991), and alate morphs are capable of making targeted landings on plants under a certain speed of prevailing wind (Goldansaz & McNeil, 2006), which indicates that wind probably is an important precondition for the movement of alate aphid (Chen et al, 2019a). In this way, apterous aphids significantly increased their thermal tolerance in feeding treatment compared to alate adults.…”
Section: Discussionmentioning
confidence: 99%
“…During the feeding experiment, we observed that most of the alate adults remained stationary in the transparent plastic box, rather than moving to the barley seedlings as quickly as the apterous phenotypes. As we know, walking is the main way of apterous aphids moving to nearby plants in the field (Nottingham et al ., 1991), and alate morphs are capable of making targeted landings on plants under a certain speed of prevailing wind (Goldansaz & McNeil, 2006), which indicates that wind probably is an important precondition for the movement of alate aphid (Chen et al, 2019a). In this way, apterous aphids significantly increased their thermal tolerance in feeding treatment compared to alate adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, intermorph variation is demonstrated in relation to the olfactory cue. Indeed, the olfactory cue is perceived by sensory structures called rhinaria located on the tips of aphid antennae [16]. Wingless aphids are equipped with primary rhinaria, i.e., detecting only host plant odours, whereas the winged individuals have secondary rhinaria, which are more evolved, perceiving host and non-host volatile chemicals [16].…”
Section: Pre-contactmentioning
confidence: 99%
“…Indeed, the olfactory cue is perceived by sensory structures called rhinaria located on the tips of aphid antennae [16]. Wingless aphids are equipped with primary rhinaria, i.e., detecting only host plant odours, whereas the winged individuals have secondary rhinaria, which are more evolved, perceiving host and non-host volatile chemicals [16]. This would be due to the fact that winged aphids fly over a broader range of plant species that they need to be able to distinguish from their host plant on which they should land [17].…”
Section: Pre-contactmentioning
confidence: 99%
“…Although few innovations happened in reducing the damage caused by insects through biotechnology and Integrated Pest Management procedures [60]. In case of biotechnology there is considerable reduction in the pest activity and damage by killing the pests by genetic engineering and also releasing Bt crops , Eg.…”
Section: Arbuscular Mycorrhizal Fungi and Vegetable Insect Controlmentioning
confidence: 99%